Corporate social responsibility - a new perspective in coping with the unemployment at local level - Srbinoska, Sladjana (Ревија за социјална политика/Journal of Social Policy, 2012)
Challenged with global problems, including the economic crises and natural disasters, the concern about the local problems is left to the local communities’ ability to deal with it. The local communities depend on their ability and creativity to utilize the local resources in dealing with local issues, like unemployment, social protection or the social wellbeing. With the globalization, many companies recognized the need to obtain local support for their businesses. They are aware that local support means improved social image, better rating, more committed employees and growing potential.With this in mind, these companies devote their time and resources to initiate community development projects, create possibilities for voluntary work, offer continued education and training for youth and adults, and provide support for skills’ development programs. Recently, we have witnessed pioneering efforts by some of the local businesses to invest in the local communities in the Republic of Macedonia. In 2010, the recently established Coordinating Committeefor Corporate Social Responsibility awarded 15 Macedonian companies out of 75 nominated for corporate social interventions in their communities. These companies implemented certain social interventions aimed to: offer employment to children without parents and parental care , provide fellowships for educational degree, initiate programs for social inclusion, trainings for entrepreneurship and skills development and investing in infrastructural improvements in the communities. This paper will try to answer the question: Can the corporate social responsibility and the corporate community investment have an influence in lowering the level of local unemployment? The paper will present comparative experiences from Europe and USA on recent trends in corporate community investment, and will present examples of socially responsible practices in coping with the unemployment. An emphasis willbe given to the potential of coordinated effort between the current government employment programs and the possibilities that the businesses offer in the Republic of Macedonia. Can we state that the social corporate responsibility is a new perspective in dealing with social problems, including the local unemployment?
Keywords: corporate social responsibility; community investment; unemployment; socially responsible practices